2004
DOI: 10.1097/01.asn.0000117977.14912.91
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Echocardiographic Indicators of Left Ventricular Systolic Function in Asymptomatic Dialysis Patients

Abstract: Abstract. Patients with end-stage renal disease (ESRD) are at high risk for heart failure, but the prevalence and the prognostic value of asymptomatic systolic dysfunction in these patients are unknown. In this prospective cohort study, the authors have therefore assessed by echocardiography the prevalence and the prognostic value of systolic function as estimated by ejection fraction (EF), fractional shortening at endocardial level (endoFS), and at midwall (mwFS), in a cohort of 254 asymptomatic dialysis pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
147
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(158 citation statements)
references
References 38 publications
9
147
1
1
Order By: Relevance
“…Zoccali et al 7 in a study of 254 hemodialysis patients, Rakhit et al 35 in a study that included 176 patients with CKD stages 4 and 5 on conservative treatment or dialysis, and Cheung et al 22 in the HEMO multicenter study, described a similar result in the final model of Cox multivariate analysis.…”
Section: Siqueira Et Al Doppler Echocardiogram In Hemodialysis Patientssupporting
confidence: 50%
See 2 more Smart Citations
“…Zoccali et al 7 in a study of 254 hemodialysis patients, Rakhit et al 35 in a study that included 176 patients with CKD stages 4 and 5 on conservative treatment or dialysis, and Cheung et al 22 in the HEMO multicenter study, described a similar result in the final model of Cox multivariate analysis.…”
Section: Siqueira Et Al Doppler Echocardiogram In Hemodialysis Patientssupporting
confidence: 50%
“…Evidence indicates that the LV systolic dysfunction parameters are independently associated with the occurrence of fatal and nonfatal cardiovascular events in patients on dialysis, with no difference in predictive power between the methods used to evaluate it 7 . In this study, we observed, at univariate analysis, that reductions in EF or systolic fractional shortening are related to increased risk of cardiovascular events.…”
Section: Survival Function Censoredmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The adverse effect of systolic dysfunction does not dependent on left ventricular mass, but both alterations interact in predicting cardiovascular outcomes, and reach maximum risk in patients with an association of both. 22 Diastolic dysfunction is present in most individuals on renal replacement therapy. Recent data emphasize the importance of estimating the severity of diastolic dysfunction in a non invasive way, identifying patients evolving with an elevation in filling pressures (advanced diastolic dysfunction, that is, grades II and III).…”
Section: Morphofunctional Alterationsmentioning
confidence: 99%
“…Anemia, mineral and bone disorders, the inflammation-muscular-wasting complex, cardiomyopathy, neuropathy, and depression, all disturbances that frequently coexist in CKD-5D, may be involved in the poor physical functioning of this population (3)(4)(5)(6). Pulmonary congestion detected and quantified by lung ultrasonography recently emerged as a powerful correlate of poor physical functioning in a multicenter study in peritoneal dialysis (PD) patients (7), a population with an exceedingly high prevalence of fluid overload and left ventricular dysfunction (8)(9)(10), suggesting that volume expansion and cardiomyopathy, two potentially reversible risk factors, play a major role in the poor physical performance of this population.…”
Section: Introductionmentioning
confidence: 99%